1987
DOI: 10.1104/pp.84.2.421
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Partial Characterization of the Lipopolysaccharides from Several Rhizobium trifolii Mutants Affected in Root Hair Infection

Abstract: ABSTRACIrThe lipopolysaccharides (LPSs) from Rhizobium trifolii ANU843 and several transposon (Tn5) symbiotic mutants derived from ANU843 were isolated and partially characterized. The mutant strains are unable to induce normal root hair curling (Hac-phenotype) or nodulation (Nodphenotype) in clover plants. The LPSs from the parent and mutants are very similar in composition. Analysis by PAGE shows that the LPSs consist of higher and lower molecular weight forms. The higher molecular weight form of the LPSs ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…phaseoli and R. leguminosarum bv. trifolii, it was shown that this high-molecular-weight fraction corresponds to LPSI containing the 0-antigen side chain (7,8). To decide whether the mutants described here completely lack the LPSI or produce very reduced quantities, a more sensitive immunoblotting assay would be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…phaseoli and R. leguminosarum bv. trifolii, it was shown that this high-molecular-weight fraction corresponds to LPSI containing the 0-antigen side chain (7,8). To decide whether the mutants described here completely lack the LPSI or produce very reduced quantities, a more sensitive immunoblotting assay would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…trifolii (previously called R. trifolit) (8,34,35). Similarly, quantitative differences in the LPS of a Nodmutant of a fast-growing Rhizobium japonicum strain were observed (9).…”
mentioning
confidence: 99%
“…The surface carbohydrates of rhizobia, which include the lipopolysaccharide (LPS), extracellular polysaccharide, and capsular polysaccharide, have all been hypothesized to play a role in symbiosis (9,11,18,20,22,23). The LPSs of Rhizobium species resemble their enterobacterial counterparts in having structurally distinct regions; the 0-chain polysaccharide, the core oligosaccharide, and the hydrophobic lipid A (10,(13)(14)(15)(16)(17); however, there are many differences in the structural details of Rhizobium LPSs compared with enterobacterial LPSs (1-3, 12, 25-27).…”
mentioning
confidence: 99%
“…trifolii (16,50,51) and Rhizobium fredii (17) after the loss of whole plasmids. Various mutants with alterations in LPS were defective in the symbiotic association at different stages of development.…”
mentioning
confidence: 99%
“…By a different approach, in an attempt to characterize the participation of LPS in symbiosis, changes in the composition of LPS were found among nodulating and nonnodulating strains of Rhizobium leguminosarum bv. trifolii (16,50,51) and Rhizobium fredii (17) after the loss of whole plasmids. Various mutants with alterations in LPS were defective in the symbiotic association at different stages of development.…”
mentioning
confidence: 99%